(untitled) - Musevic, I. (Singapore, 2000)
In this book the basic physics of ferroelectric liquid crystals is presented in a transparent way together with the linear and non-linear optics of these systems. Specific attention is paid to the applications of ferroelectric liquid crystals as electro-optic modulators, matrix displays, optical logic gates, optical phase conjugation devices, elements for optical computing and erasable optical memories. A special chapter is devoted to polymer ferroelectric liquid crystals.
Keywords: Ferroelectric crystals,Tính chất điện từ